Self-Control, Sanction Threats, Temptation, and Crime: Examining Contingencies of Self-Control in a Cross-National Context. (April 2019) - Cihan, Abdullah; Tittle, Charles R.
Using a representative household survey data, we examine the generality of self-control, the predictive strengths of sanction threats, and the interaction between criminal propensity and sanction threats in explaining criminal probability. Although the data confirm the generality of self-control predictions of deviant/criminal behavior in the Turkish cultural context, the effects appear quite modest and contingent on fear of informal sanctions and temptation. Consistent with the findings of recent studies, a small interaction between self-control and sanction threats suggests that deterrence is greatest among individuals with weak self-control. However, there is no interaction between sanction threats and temptation, suggesting that sanction fear is equally likely among individuals regardless of their level of temptation.